Path Planning for Construction Robot Based on the Improved A* Algorithm and Building Information Modeling - Dejiang Wang; Bolong Liu; Haili Jiang; Panpan Liu (Buildings)
Path planning is a key technology in the automation of construction robots, and its implementation mainly relies on navigation algorithms and the generation of environment maps. However, the original A* algorithm has issues such as not considering dimensional constraints, a high number of turning nodes, and unsmooth paths. Moreover, traditional environment map generation is time-consuming and energy-consuming. Therefore, this paper proposes a path-planning method for construction robots based on an improved A* algorithm and BIM. First, the A* algorithm is improved by incorporating dimensional constraints for both the building and the robot and by reasonably setting virtual obstacles to enhance the feasibility of robot movement. Additionally, B-spline curves are used to optimize the path, reduce turning points, and achieve a smoother trajectory. Second, Dynamo visual programming is used to process the building’s BIM model, enabling efficient generation of the environment map while preserving the rich semantic and geometric information of the building. Finally, the improved A* algorithm is employed to perform path planning within the environment map generated from the BIM model, resulting in the generation of the optimal path. Through experimental verification on the civil engineering building of a university, the results show that the improved A* algorithm can successfully navigate within the BIM-generated map. It not only ensures the safety and smoothness of path planning but also enables the fast and efficient generation of environment maps. This effectively advances the research and application of BIM technology in the field of robot navigation.